A Bit O' White. - Buckingham, Anne; Tilman (Brussels : CCNOA center for contemporary non-objective art, 2007)
Alessandra, Matilde ; Benson, Tom ; Dashper, Julian ; de Bièvre, Guy ; Denys, Ward ; Fried, Zipora ; Kloosterboer, Klaas ; Levi, Renée ; Miller, Gerold ; Roberts, Perry ; Skoda, Michal ; Stolte, Clary ; van der Ploeg, Jan ; Vermeersch, Pieter ; Villard, Emmanuelle ; Voskuil, Jan Maarten
A Bit O' White = Een beetje wit = Un peu de blanc, CCNOA center for contemporary non-objective art, Brussels, 16/03/2007 - 29/04/2007
boek